The Effect of Rural Banditry on Food Security in Nigeria: A Case of Ovia North-East Local Government Area, Edo State - Amadasu , Andrew Ikponmwosa; Etinosa, Osaghae Jonathan (Kashere Journal of Politics and International Relations, 2024)
The farmer-herder crisis is one of the major insecurities facing Nigeria today. Though not a recent phenomenon, it has snowballed into a hydra-headed scourge that appears to be threatening the continued existence of Nigeria. Several theories account for its existence: climate change, corruption, poverty, ethnicity, Muslim-ideology, urbanization, contracting land spaces, Anti-Open Grazing Laws and others. In all these, ostensible realities of daily casualties, kidnapping, rape and destruction of crops cannot be under-reported. It is in the face of these realities that the study examined the effect of farmer-herder crisis on food security in Edo State, using Ovia North East as a case study. The study utilized semi-structured questionnaire to elicit responses from four sampled communities (Uhiere, Osasimwinoba, Odighi and Okokuo) in the sampled LGA. An initial 200 questionnaires were distributed but only 188 were returned. Based on these findings, the study therefore recommended that there is need for the government to tackle poverty in the Northern part of the country, there is need for the security agents are not living up to their billing in terms of tackling the crisis, there is need for the government implemented state and community policing and the need for the government (both federal and state) to make policies towards cushioning the effect of rising food inflation in Nigeria.